2020
DOI: 10.14309/ctg.0000000000000162
|View full text |Cite
|
Sign up to set email alerts
|

Short-Course Radiotherapy in Locally Advanced Rectal Cancer

Abstract: INTRODUCTION: To date, we do not know the best therapeutic scheme in locally advanced rectal cancer when patients are older or have comorbidities. METHODS: In 2009, we established a prospective treatment protocol that included short-course preoperative radiotherapy (RT) with standard surgery +/− chemotherapy in frail patients, mostly older than 80 years or with comorbidities. RESULTS: We included 87 patients; the mean follow-up was 43.5 months (0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…However, it should be noted that the percentage of patients who received only chemotherapy or RT alone was low. In addition, as previously described in the literature, 24,34 no differences have been found between short-course and long-course neoadjuvant RT in terms of long-term oncologic outcomes. We found that patients with CRM+ had a higher risk of LR than those with CRM−.…”
Section: Discussionsupporting
confidence: 63%
“…However, it should be noted that the percentage of patients who received only chemotherapy or RT alone was low. In addition, as previously described in the literature, 24,34 no differences have been found between short-course and long-course neoadjuvant RT in terms of long-term oncologic outcomes. We found that patients with CRM+ had a higher risk of LR than those with CRM−.…”
Section: Discussionsupporting
confidence: 63%
“…The former involves the administration of a total of 45 Gy delivered by daily 2.8–2 Gy over the course of 5 weeks with concomitant 5-FU based chemotherapy followed by planned resection in 6–8 weeks after completion. The latter includes the delivery of 5x 5 Gy over the course of 1 week with planned surgery in the following week [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…LCCRT and SCRT have largely demonstrated similar results when assessing the rates of 5-year distant recurrence (27–30%),5-year survival (70–74%)and late adverse grade 3–4 toxicity (5.8–8.2%) [ 17 ]. The comparable efficacy of SCRT and reduced toxicity means that it is considered an equally effective option in treatment of locally advanced rectal cancer in the frail patient population in whom chemotherapy associated toxicity may pose further delays to the start date of surgery [ 16 ]. Recently, the effect of differing intervals between neoadjuvant therapy and surgery and its effect on oncological outcomes and complication profile has been subject of ongoing research.…”
Section: Introductionmentioning
confidence: 99%
“…TME is the gold standard in rectal cancer surgery and is comprised of resection of the rectum together with the fatty tissue surrounding the rectum [45]. For LARC, therapy consists of preoperative chemo-radiation therapy (pCRT) or radiotherapy alone followed by TME [51][52][53][54][55][56][57][58][59][60][61][62].…”
Section: Discussionmentioning
confidence: 99%